The Life Story Experience of "Migrant Dentists" in Australia: Potential Implications for Health Workforce Governance and International Cooperation - Madhan Balasubramanian; A. John Spencer; Stephanie D. Short; Keith Watkins; Sergio Chrisopoulos; David S. Brennan (Kerman University of Medical Sciences, 2017)
Background The migration of dentists is a major policy challenge facing both developing and developed countries. Dentists from over 120 countries migrate to Australia, and a large proportion are from developing countries. The aim of the study was to assess the life story experience (LSE) of migrant dentists in Australia, in order to address key policy challenges facing dentist migration. Methods A national survey of all migrant dentists resident in Australia was conducted in 2013. Migrant experiences were assessed through a suite of LSE scales, developed through a qualitative-quantitative study. Respondents rated experiences using a five-point Likert scale. Results A total of 1022 migrant dentists responded to the survey (response rate = 54.5%). LSE1 (health system and general lifestyle concerns in home country), LSE2 (appreciation towards Australian way of life) and LSE3 (settlement concerns in Australia) scales varied by migrant dentist groups, sex, and years since arrival to Australia (chi-square, P < .05). In a logistic regression model, migrants mainly from developing countries (ie, the examination pathway group) faced greater health system and general lifestyle concerns in their home countries (9.32; 3.51-24.72) and greater settlement challenges in Australia (5.39; 3.51-8.28), compared to migrants from well-developed countries, who obtained direct recognition of qualifications. Migrants also are more appreciative towards the Australian way of life if they had lived at least ten years in Australia (1.97; 1.27-3.05), compared to migrants who have lived for less than ten years. Conclusion Migrant dentists, mainly from developing countries, face challenges both in their home countries and in Australia. Our study offers evidence for multi-level health workforce governance and calls for greater consensus towards an international agenda to address dentist migration. Better integration of dentist migration with the mainstream health workforce governance is a viable and opportunistic way forward.